Land Trafficking, Speculative Urban Growth and Governance of the Peripheries of Lima: The Pasamayito-San Juan de Lurigancho Case - Dammert-Guardia, Manuel (2025)
Based on the case of the vial project of Pasamayito, from its irregular creation (2001) to its pavement (2022), we discuss the configuration of the modes of urban growth and governance in Metropolitan Lima in the 21st century. We conclude that there is speculative urban growth because the logic of the actors dynamizing the submarket of land is sustained by legislation and state interventions. This implies discussing urban governance in the overlapping processes of boundary conflict, land grabbing and public investment projects, which are interdependent, operate with degrees of simultaneity and reproduce adverse conditions and social disadvantages for those who live there.